2022
DOI: 10.31234/osf.io/7aj5h
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

[PhD Dissertation] Good Research Practices

Abstract: In this dissertation, I examine research practices and reform ideas aiming to combat the crisis of confidence in psychology (Pashler & Wagenmakers, 2012). I do so through theoretical contributions and empirical work, propose practical guidelines for researchers, and demonstrate how principles of good research can be conveyed to students. The research methods and statistical practices I present facilitate the adherence to the following three principles: (1) respect the empirical cycle; (2) acknowledge u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 324 publications
0
1
0
Order By: Relevance
“…Thus, medicalization happens when new power relations are filtered through any social arena that institutionalizes medical knowledge. Recent studies have demonstrated that, in cases involving multiple sources of expertise, medicalization intertwines with other processes, such as decriminalization (Greil et al 2020; Lin 2017; Rafalovich 2020; Sundaram 2019). The result is hybrid institutional concepts and practices.…”
Section: (Bio)medicalization (De)criminalization and The Penal-medica...mentioning
confidence: 99%
“…Thus, medicalization happens when new power relations are filtered through any social arena that institutionalizes medical knowledge. Recent studies have demonstrated that, in cases involving multiple sources of expertise, medicalization intertwines with other processes, such as decriminalization (Greil et al 2020; Lin 2017; Rafalovich 2020; Sundaram 2019). The result is hybrid institutional concepts and practices.…”
Section: (Bio)medicalization (De)criminalization and The Penal-medica...mentioning
confidence: 99%